INFORMATION NEEDS ASSESSMENT FOR SMALL SCALE BUSINESS COMMUNITY IN ZAMBIA: CASE STUDY OF CHISOKONE M - Banda, Charles; M. Mutula, Stephen; Grand, Balulwami (Malaysian Journal of Library and Information Science, 2017)
This paper presents the findings of a study that was carried out to determine the information needs of small-scale business community at Chisokone Market in the city of Kitwe in Zambia. The study sought to establish among other things the unique information needs of the business community; the types of businesses carried out, the different service providers within the city of Kitwe, the problems faced by small- scale business community in seeking for information and the demographic characteristics of the community. The research design employed the survey method. Questionnaires were used to collect data from the population. From a sample of 250 respondents, 209 completed questionnaires giving a response rate of 83.6%. The results of the study showed that most of the information needs related to marketing, sources of supplies, management skills, and credit /loan facilities. Lack of access to information was cited as the major problem facing small-scale businesses at Chisokone Market in Kitwe Zambia.